Metabolic Profile of Female Student in Senior High School of Metro City, Lampung, Indonesia - Aprina, Aprina; Astuti, Titi; Sulistianingsih, Eka (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Adolescent girls are a crucial period in a woman's life. Health and nutritional status during adolescence are important for physical maturity, according to data from Riskesdas (2018) Metro City has a prevalence of very thin 1.2%, underweight 8.9%, normal 88.5, and obese 1.4%. is basic research that produces new theories, methods, or policy principles that are used for scientific development, namely the description of the Metabolic Profile of Young Women Against the Menstrual Cycle at SMA Negeri Metro City. The type of quantitative research with a quantitative research design with a descriptive approach to the population in this study were young women at Senior high school public Metro City. The instruments used in this study were questionnaires and Anthropometric (BMI) examination tools, Hb, Lipid Profile (Triglycerides, HDL, LDL and cholesterol) and GDS, data analysis in this study was a Univariate test. The results showed that there were 28 (18.5%) adolescents with low HB less than 12 g/dL, 25 (16.6%) adolescents with high cholesterol less than 200 mg/dL, 25 (16.6%) adolescents with metabolic status. skinny (-3 SD for SD less than-2) as many as 51 (33.8%), teenagers with less energy as much as 65 (43.0%), lack of fat as much as 55 (36.4%) lacking protein as much as 5 (33.8 %), and less carbohydrates as much as 26 (17.2%), it is hoped that the school will cooperate with the local Health Office and local health centres to provide counselling about anemia and obesity in order to reduce the prevalence of anemia in adolescent girls and its incidence. obesity and it is necessary to educate adolescents about obesity prevention for reproductive health.